2005
DOI: 10.3748/wjg.v11.i29.4604
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of serum cholinesterase in patients with gastric cancer

Abstract: Serum CHE activity has a close relation with the incidence of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Furthermore, reductions in serum BChE can be found in various clinical conditions, such as injury, liver damage, infectious disease, and malnutrition [ 20 ]. During more recent years, a decrease in BChE could be observed in various malignancies [ 21 26 , 33 ]. The most important finding of our study was the association between low serum BChE levels and shorter PFS, CSS, and OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reductions in serum BChE can be found in various clinical conditions, such as injury, liver damage, infectious disease, and malnutrition [ 20 ]. During more recent years, a decrease in BChE could be observed in various malignancies [ 21 26 , 33 ]. The most important finding of our study was the association between low serum BChE levels and shorter PFS, CSS, and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, decreased serum BChE levels have been observed in various clinical conditions, such as stress, chronic inflammation, and malnutrition [ 20 ]. In addition, low serum BChE levels seem to be indicative of advanced tumor stage and poor prognosis in various forms of cancer, including gastric [ 21 ], renal [ 22 ], upper urinary tract [ 23 ], prostate [ 24 ], and head and neck cancer [ 25 , 26 ]. In cervical cancer, two studies in small series of patients have reported on an association between low serum BChE levels and advanced tumor stage, and have suggested a correlation between the increase in serum BChE levels and a response to radiotherapy [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In advanced liver cancer with or without hepatic involvement there is mild to moderate infl ammation and various degree of protein energy malnutrition resulting the level of pseudocholinesterase to decrease but in cirrhosis of liver pseudocholinesterase level would decrease very much when the number of functional parenchymal cells of liver decreases. Similarly in infective hepatitis the liver cells are damaged but hepatocytes are not decreased as compared to cirrhosis or carcinoma of liver 18,21 . Similar fi nding were also found by S Venkata Rao et al (2011) 21 and also by MG Khan (1962) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation has been described to be associated with poor prognosis in a variety of malignancies [16]. Plasma BChE levels have been shown to decrease in advanced cancer patients with or without hepatic involvement, despite the other liver function tests yielding normal results [17]. One of the possible mechanisms for such BChE activity decrease in cancer patients could be secondary anorexia accompanying malignancy [18].…”
Section: Discussionmentioning
confidence: 99%